2014
DOI: 10.3126/ajms.v6i2.10584
|View full text |Cite
|
Sign up to set email alerts
|

Detection of protein glycation inhibitory potential of nine antidiabetic plants using a novel method

Abstract: Background: Protein glycation is a major cause of chronic diabetic complications. Medicinal plants with protein glycation inhibitory potential will be benefi cial to prevent or delay diabetic complications. Objective: The objective of the study was to analyze protein glycation inhibitory potential of ten plants among which nine are well known for their antidiabetic effects.Methods: Methanol extracts were prepared using parts from nine plants namely, Coccinia grandis, Ficus racemosa, Gymnema lactiferum, Gymnema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…Even though, in previous reports, the plant samples were extracted using different solvents, as opposed to the aqueous extraction in our study, these reports found that antioxidative agents contributed to anti-glycation activities, while the ethanolic extracts of P. emblica fruit collected from Thailand and Saudi Arabia exhibited high antioxidant and anti-glycation activities [ 14 , 15 ]. Similar results were observed in the methanolic extract of P. emblica fruit from Sri Lanka, with the highest anti-glycation activity among nine antidiabetic plant extracts [ 16 ]. The most abundant phenolic detected in our P. emblica , gallic acid, was also able to inhibit advanced glycation end-products in both cell cultures and animal models [ 17 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 77%
“…Even though, in previous reports, the plant samples were extracted using different solvents, as opposed to the aqueous extraction in our study, these reports found that antioxidative agents contributed to anti-glycation activities, while the ethanolic extracts of P. emblica fruit collected from Thailand and Saudi Arabia exhibited high antioxidant and anti-glycation activities [ 14 , 15 ]. Similar results were observed in the methanolic extract of P. emblica fruit from Sri Lanka, with the highest anti-glycation activity among nine antidiabetic plant extracts [ 16 ]. The most abundant phenolic detected in our P. emblica , gallic acid, was also able to inhibit advanced glycation end-products in both cell cultures and animal models [ 17 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 77%
“…Previously we have analyzed antiglycation effects of the same extracts of nine antidiabetic plants and GL [ 14 ] using a different method in which bovine serum albumin (BSA) was taken as the model protein [ 15 ]. Our previous findings showed promising antiglycation effects in PD whole plant, PE fruit and PM latex [ 14 ]. Furthermore extracts of FR stem bark, GS leaf, MP yam and TC leaf also showed almost complete inhibition of glycation at 2 mg/ ml.…”
Section: Discussionmentioning
confidence: 99%
“…As per up-to-date literature, there are no reports on glycation induced protein cross-link inhibitory effects or antiglycation effects of FR, GS, PD and SP other than our recent report on antiglycation effects [ 14 ]. Among these four plant parts, evidence for a strong glycation induced cross-link inhibitory effect was obtained for PD (whole plant) in the present study .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the b cell regeneration in the pancreas [48,49] , insulin release [50,51] , insulin like action [52,53] , increased expression of glucose transporter [54] , inhibition of digestive enzymes amylase and glucosidase (by the latex) [55,56] are some of the mechanisms identified. Furthermore, evidence on protective effects such as antioxidant effects [57] , antidyslipidaemic effects [57][58][59] and evidence for antiglycation effects of the latex are available [60,61] . Several compounds responsible for the antidiabetic effects of Pterocaipus Marsupium have been revealed.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%